The relation between neutrophil/lymphocyte and platelet/lymphocyte ratios with mortality and limb amputation after acute limb ischaemia. (April 2022) - Pasqui, Edoardo; de Donato, Gianmarco; Giannace, Giovanni; Panzano, Claudia; Alba, Giuseppe; Cappelli, Alessandro; Setacci, Carlo; Palasciano, Giancarlo
Objective: Acute limb ischaemia is still considered a significant event, with considerable early- and long-term amputation and mortality risk. Our study aims to investigate the predictive role of pre-operative neutrophil/lymphocyte and platelet/lymphocyte ratios in terms of mortality and amputation risk in patients with acute limb ischaemia. Methods: Pre-operative blood samples of all patients admitted with acute limb ischaemia were used to calculate neutrophil/lymphocyte and platelet/lymphocyte ratios. Population was subdivided into quartiles by platelet/lymphocyte ratio and neutrophil/lymphocyte ratio values, and Kaplan-Meier life tables were obtained for overall survival and limb salvage. The optimal neutrophil/lymphocyte ratio and platelet/lymphocyte ratio cut-offs were obtained from receiver operating characteristic curves with all-cause mortality and all kinds of amputation. Stepwise multivariate analysis was performed in order to identify independent risk and protective factors for mortality and amputations. Results: A total of 168 patients were included in the analysis. Receiver operating characteristic curves identified cut-off values for neutrophil/lymphocyte ratio and platelet/lymphocyte ratio: neutrophil/lymphocyte ratio ≥5.57 for mortality; neutrophil/lymphocyte ratio ≥6.66 and platelet/lymphocyte ratio ≥269.9 for all amputations. Kaplan-Meier analysis revealed that survival rate in group neutrophil/lymphocyte ratio <5.57 was 83.4%, 78.9%, 73.7%, and 59.8%, respectively, at 12, 24, 36, and 48 months; in neutrophil/lymphocyte ratio ≥5.57 group was 62.4%, 51.3%, 47.8, and 43.7%, respectively ( p < 0.0001). Freedom from all amputations was significantly higher in case of neutrophil/lymphocyte ratio and platelet/lymphocyte ratio below the identified cut-off values ( p < 0.0001). Neutrophil/lymphocyte ratio and platelet/lymphocyte ratio were found as independent risk factors. Conclusion: Neutrophil/lymphocyte ratio and platelet/lymphocyte ratio are reliable markers for stratification of mortality and limb amputations in patients with acute limb ischaemia. The inexpensive nature and ready availability of these biomarkers' values reinforced their usefulness in everyday clinical practice.